Pemerkasaan nilai dan profesionalisme menerusi penghayatan Al-Asma’ Al-Husna: analisis pemikiran Al-Ghazali dalam Al-Maqsad Al-Asna Fi Syarh Ma’ani Asma’ Allah Al-Husna - Mohd FauziHamat, (Universiti Kebangsaan Malaysia, 2009)
This article analyses al-Ghazali’s thoughts on The Beautiful Names of God (al- Asma’ al-Husna) in his book, al-Maqsad al-Asna fi Syarh Ma‘ani Asma’ Allah al-Husna. The author highlighted al-Ghazali’s ideas on strengthening ethical values and professionalism based on al-Asma’ al-Husna such as al-Rahman, al-Quddus, al-Salam, al-Ghaffar, al-‘Adl, al-Latif and others. This article concludes by suggesting that if all values of the al-Asma’ al-Husna such as being passionate to others, caring, helpful, objective in thinking and actions, willing to give and able to forgive others are properly understood and implemented, one could demonstrate good professional and ethical values in his daily life